Synthesize and Application of Fe3O4/MW-CNT Composite in Photo-Catalyst Assisted Electrochemical Oxidation of BTX Compounds from Wastewater - Arsalan Parvareh; Mohammad Ghanbarnezhad; Mostafa Keshavarz Moraveji; Sahand Jorfi (Iranian Journal of Chemical Engineering)
The Fe3O4/MW-CNT composite was prepared for a hybrid photo-catalyst-assisted electrochemical process for the removal of BTX contamination from wastewater. Oxidation of multi-walled carbon nanotube was conducted by different treatments including acid treatment and hydrogen peroxide. The XRD, FTIR, SEM, TEM, and BET analyses were performed to characterize both the MW-CNT and the synthesized composite. Simultaneous photo-catalyst and electrochemical processes were conducted to evaluate the performance of a new hybrid process for wastewater treatment. The effect of current density, photo-catalyst loading, and BTX initial concentration was investigated experimentally. The characterization results of the synthesized composite show that a mixture of strong nitric acid and sulfuric acid treatment at a high exposure time and low temperature is the best route for MW-CNT oxidation. The removal efficiency of BTX compounds from wastewater using the hybrid photo-electrochemical process was found to be in the range of 28 to 43% for different conditions. The optimum condition for maximum removal of BTX was found by mathematical modeling of experimental data. The results indicate that a combination of photo-catalyst and the electrochemical process can enhance the BTX removal efficiency.